Proposed new schematic design for manga gallery for viz media at Cineleisure Damansara / Nur Farhana Suhaimi - Suhaimi, Nur Farhana (Faculty of Architecture, Planning and Surveying, 2008)
More and more manga and manga-based anime are brought into our country from the Land of the Rising Sun, Japan; translated into either Malay or into English language. Manga reading, anime watching and cosplaying (manga and anime costume playing) culture in Malaysia is growing gradually day by day. Even so. unlike in Japan, there is not until now a special spot for these fans to read as many manga as they like, meet other manga fans, in their favorite manga characters costumes (or not); and share common interests, here. Therefore, this manga gallery project is to fill the emptiness of a manga fan’s heart. The client of said project is Viz Media, a California-based publishing company. From its establishment in 1986, Viz Media has been importing a lot of fame-climbing manga volumes and weekly manga magazines from Japan and translating them into English to introduce this culture to the people of United States. This first ever proposed manga gallery in Malaysia is located at the first floor of newly renovated MARA Headquarters on Jalan Sultan Ismail, which can be accessed easily by visitors since it is a public zone since the ground floor up to the second floor have always been allocated for business premises. About the surrounding of the manga gallery site, it is surrounded by offices, shopping malls and shopping complex, such as Maju Junction, Pertama Complex and SOGO. In other words, a lot of people either work or go to these places and thus, manga gallery will attract these people to go to this gallery. Talking about concept, this manga gallery takes the concept of “Heaven Fantasy”, a concept that will make the manga fans to feel they belong somewhere, the manga heaven- a peek of the almost fantasy they have always thought of only happen in manga and anime but now it is them to feel.